AWARENESS OF HUMAN PAPILLOMA VIRUS AND VACCINE AMONG INDIAN LGBTQ+ INDIVIDUALS: A SURVEY STUDY - Swara Arya; Sakshi Raj; Sajjad Alam (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Human papillomavirus (HPV) is a prevalent sexually transmitted infection that can lead to various health complications, including cervical cancer and genital warts. While HPV vaccination is widely recommended for preventing HPV-related diseases, awareness and knowledge of the vaccine among marginalized populations, such as the Indian LGBTQ+ (Lesbian, Gay, Bisexual, and Transgender) community, remain understudied. Understanding the awareness and perceptions of HPV and its vaccine within this community is crucial for developing targeted public health interventions.Materials & Methods: This survey study aimed to assess the level of awareness and knowledge of HPV and its vaccine among Indian LGBTQ+individuals. A structured questionnaire was designed to collect data on participants' demographic characteristics, awareness of HPV, knowledge about the HPV vaccine, and attitudes toward vaccination. The survey was distributed online through LGBTQ+ community forums and social media platforms to reach a diverse sample of Indian LGBTQ+ individuals. Participants were assured of confidentiality and voluntary participation.Results: The study received responses from a diverse group of Indian LGBTQ+ individuals. The results revealed varying levels of awareness and knowledge about HPV and its vaccine within the community. A significant proportion of participants had limited awareness of HPV-related diseases and the availability of HPV vaccines. Moreover, misconceptions and myths surrounding HPV and vaccination were prevalent among some respondents. However, there were also participants who demonstrated a good understanding of HPV, its transmission, and the importance of vaccination.Conclusion: The findings of this study highlight the need for targeted health education campaigns and interventions to increase awareness and knowledge of HPV and its vaccine among the Indian LGBTQ+ community. Improved access to accurate and culturally sensitive information about HPV vaccination is essential to empower individuals to make informed decisions about their sexual health and well-being. Health authorities and organizations should collaborate to develop tailored educational programs that address the unique needs and concerns of the LGBTQ+ population, ultimately promoting better health outcomes and reducing the burden of HPV-related diseases in this marginalized community.